2021
DOI: 10.1177/20563051211024957
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Online Amplification of COVID-19 Elites in the United States

Abstract: In the absence of clear, consistent guidelines about the COVID-19 pandemic in the United States, many people use social media to learn about the virus, public health directives, vaccine distribution, and other health information. As people individually sift through a flood of information online, they collectively curate a small set of accounts, known as crowdsourced elites, that receive disproportionate attention for their COVID-19 content. However, these elites are not all created equal: not all accounts have… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 52 publications
3
64
0
1
Order By: Relevance
“…For individual Twitter users, a more sophisticated measure of influence is used. The user influence is estimated by their retweet h-index [ 40 , 55 ], an adaptation of the well known Hirsch index [ 41 ] to Twitter. The retweet h-index takes into account the number of tweets posted, as well as the impact of individual tweets in terms of retweets.…”
Section: Methodsmentioning
confidence: 99%
“…For individual Twitter users, a more sophisticated measure of influence is used. The user influence is estimated by their retweet h-index [ 40 , 55 ], an adaptation of the well known Hirsch index [ 41 ] to Twitter. The retweet h-index takes into account the number of tweets posted, as well as the impact of individual tweets in terms of retweets.…”
Section: Methodsmentioning
confidence: 99%
“…This approach complements panel-based longitudinal studies that can be conducted at scale with regards to demographic information such as age, gender, and party affiliation 38 . Here we use influential accounts within each community as sentinel nodes, as previous work has shown that COVID-19 online content generally 20 and COVID-19 misinformation specifically 16 is driven by a small set of influential accounts. We note that other criteria for sentinel node selection, such as a mixture of influential and randomly selected accounts, may also be desirable for detection and characterization of circulating content within communities.…”
Section: Discussionmentioning
confidence: 99%
“…Note that there are many possible ways to select sentinel nodes from a given community. Here we select a subset of influential nodes from each community to use as sentinel nodes, as a majority of Twitter content is driven by a small subset of accounts 20 . Thus, there is some overlap between the selection of sentinel accounts and opinion leadership within the constituent online communities.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, the retweet h-index was first used on Twitter data in the context of Brexit, to measure the influence of the Leave and Remain proponents [20]. Later, this measure of influence was termed a retweet h-index [33], a term we also adopt here.…”
Section: Retweet H-index Influencementioning
confidence: 99%